Pd deposition on TiO2(110) and nanoparticle encapsulation. (3rd July 2015) - Bowker, Michael; Sharpe, Ryan
Abstract: The effect of sputtering, annealing and oxidation on the surface properties of TiO2 (110), and on the same surfaces with nanoparticles present, has been investigated. Sputtering the crystal clean gives a much reduced surface with Ti 2+ as the dominant species. This, surface is mainly Ti 3+, 4+ after annealing in vacuum. Oxidation reduces the surface Ti 3+ considerably. When Pd nanoparticles are annealed on any of the investigated titania surfaces the particles become encapsulated by a film of titanium oxide. This is particularly noticeable in ISS (ion scattering spectroscopy) where the Pd:Ti ratio drops by a factor of 300 after annealing to 750 K, indicating complete coverage of the Pd nanoparticles by the oxide film. This happens most easily for the nanoparticles deposited on the reduced surfaces (beginning at ~673K) but also occurs for the very oxidized surface at~773K. Thus reduced Ti from the subsurface region can migrate onto the Pd surface to form the sub-oxide, the sub-oxide being a thin TiO-like layer. Abstract :